Information Context: Nature, Impact, and Role 5th International Conference on Conceptions of Library and Information Sciences, CoLIS 2005, Glasgow, UK, June 4-8, 2005 Proceedings - Crestani, Fabio; Ruthven, Ian.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
CoLIS 5 was the ?fth in the series of international conferences whose general aim is to provide a broad forum for critically exploring and analyzing research inareassuchascomputerscience,informationscienceandlibraryscience.CoLIS examinesthehistorical,theoretical,empiricalandtechnicalissuesrelatingtoour understanding and use of information, promoting an interdisciplinary approach to research. CoLIS seeks to provide a broad platform for the examination of context as it relates to our theoretical, empirical and technical development of information-centered disciplines. The theme for CoLIS 5 was the nature, impact and role of context within information-centered research. Context is a complex, dynamic and multi- - mensional concept that in?uences both humans and machines: how they behave individually and how they interact with each other. In CoLIS 5 we took an interdisciplinary approach to the issue of context to help us understand and the theoretical approaches to modelling and understanding context, incorporate contextual reasoning within technology, and develop a shared framework for promoting the exploration of context.
Invited Papers -- Wittgenstein, Language and Information: “Back to the Rough Ground!” -- Text, Co-text, Context and the Documentary Continuum -- Representing Context -- The Sense of Information: Understanding the Cognitive Conditional Information Concept in Relation to Information Acquisition -- Practical Implications of Handling Multiple Contexts in the Principle of Polyrepresentation -- Information Sharing and Timing: Findings from Two Finnish Organizations -- Context and Relevance in Information Seeking -- Contexts of Relevance for Information Retrieval System Design -- Searching for Relevance in the Relevance of Search -- Information Searching Behavior: Between Two Principles -- Context and Information -- Bradford’s Law of Scattering: Ambiguities in the Concept of “Subject” -- The Instrumentality of Information Needs and Relevance -- Lifeworld and Meaning – Information in Relation to Context -- Contextualised Information Seeking -- Personometrics: Mapping and Visualizing Communication Patterns in R&D Projects -- Annotations as Context for Searching Documents -- Conceptual Indexing Based on Document Content Representation -- Agendas for Context -- What’s the Deal with the Web/Blogs/the Next Big Technology: A Key Role for Information Science in e-Social Science Research? -- Assessing the Roles That a Small Specialist Library Plays to Guide the Development of a Hybrid Digital Library -- Power Is Information: South Africa’s Promotion of Access to Information Act in Context -- Context and Documents -- A Bibliometric-Based Semi-automatic Approach to Identification of Candidate Thesaurus Terms: Parsing and Filtering of Noun Phrases from Citation Contexts -- Context Matters: An Analysis of Assessments of XML Documents -- Workshops -- Developing a Metadata Lifecycle Model -- Evaluating User Studies in Information Access.
Keywords: Information storage and retrieval; Application software; Database management; Natural language processing (Computer science).; Multimedia information systems; Artificial intelligence; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Database Management; Natural Language Processing (NLP).; Multimedia Information Systems; Artificial Intelligence